Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Migration Delays at Head-of-Tide Weirs are a Function of Tidal Cycles and River Flows in Anadromous Twaite Shad Alosa fallax - Mark I. A. Yeldham; J. Robert Britton; Charles Crundwell; Peter Davies; Jamie R. Dodd; Chris Grzesiok; Andrew D. Nunn; Randolph Velterop; Jonathan D. Bolland (Estuaries and Coasts, 2025)
Riverine barriers can have significant negative impacts on the spawning migrations of anadromous fishes, with barriers of low passage efficiency limiting access to upstream spawning areas. Even fish that pass a barrier can be negatively affected via migration delays and energetic costs. The spawning migrations of 74 twaite shad Alosa fallax were tracked at two head-of-tide weirs on a bifurcated channel in the River Severn’s upper estuary, western England, to test how barriers in tidal areas can affect river entry and incur migration delays. Although the weirs had a combined passage efficiency of 98.9%, median passage time was 19.8 h, with the longest passage time being 16.8 days, and those passing fastest being relatively large fish that approached during spring tides and higher river flows. A higher proportion of fish approached and passed the weir on the larger channel that generally had the dominant flow, yet the weir on the other channel had the higher probability of passage, with the effect of elevated river levels being less important, and individuals approaching this weir were less delayed. With river level being a function of the cyclical nature of the lunar and daily tidal cycles, temporal variation in passage efficiencies was predictable. As the environmental conditions that stimulated the entry of fish into the upper estuary were largely unrelated to the conditions facilitating weir passage, there was a high potential for migration delays at these barriers that potentially incurred considerable energetic costs.

Restoration of river connectivity enables long-distance spawning migrations in a potamodromous fish - Dagmara Błońska; Ali Serhan Tarkan; Demetra Andreou; Jonathan D. Bolland; Peter Davies; Jamie R. Dodd; Phillipa Gillingham; Catherine Gutmann Roberts; Fatima Amat-Trigo; Sadi Aksu; Andrew Hindes; O. Jonas Palder; et al. (Journal of Environmental Management, 2025)

Emigration of post‐spawned twaite shad Alosa fallax , an anadromous and iteroparous fish, in a highly fragmented river - Mark I. A. Yeldham; J. Robert Britton; Charles Crundwell; Peter Davies; Jamie R. Dodd; Andrew D. Nunn; Randolph Velterop; Jonathan D. Bolland (Journal of Fish Biology, 2024)
Anthropogenic barriers are widely known to negatively impact the spawning migrations of anadromous fishes, by delaying or preventing passage upstream. Although the impacts of barriers on emigrating post‐spawned adults are less well studied, they could potentially impact the fitness and subsequent return rates of iteroparous species. In this study, passive acoustic telemetry was used to track the emigrations of 53 twaite shad Alosa fallax in the River Severn basin in their first spawning migration a year after being tagged, giving insights into their emigration movements and the impacts of anthropogenic weirs on these movements. A. fallax began their emigrations after spending varying amounts of time and migrating various distances within the river, with late‐emigrating individuals moving fastest and most directly. Emigrations became faster and more direct the further downstream individuals were from their furthest upstream extent. Downstream passage delays at weirs increased emigration times by a median of 61%, with environmental conditions (i.e., temperature, flow, and tidal influence on river level) having little influence on downstream passage at weirs with no modifications to facilitate fish passage. As weir‐induced emigration delays are suggested to deplete energy reserves (when energy levels are already depleted post‐spawning), limit spawning opportunities (by preventing access to downstream spawning habitat), and expose individuals to increased predation risk and suboptimal conditions (e.g., high temperatures), these delays can potentially diminish the benefits of iteroparity. The evidence presented here suggests that more consideration should be given to the potential impacts of anthropogenic barriers on the emigrations of iteroparous species when assessing river connectivity or undertaking barrier mitigation.

Individual repeatability in the timing of river entry indicates the strong influence of photoperiod in the spawning migrations of iteroparous twaite shad Alosa fallax - Mark I. A. Yeldham; J. Robert Britton; Charles Crundwell; Peter Davies; Jamie R. Dodd; Andrew D. Nunn; Randolph Velterop; Jonathan D. Bolland (Hydrobiologia, 2023)
The timing of entry into freshwater by mature anadromous fishes is an important component of their migration phenology. In iteroparous anadromous species, identifying the migration cues that influence the timing of entry into freshwater, and annual variability in these timings, is important in assessing the extent of individual repeatability. Here, passive acoustic telemetry tracked 71 twaite shad Alosa fallax (‘shad’) returning to the River Severn’s upper estuary over successive spawning seasons, providing individual information on river entry timing and the associated migration cues. The timing of shad returning to the river (defined as their first detection on an acoustic receiver in the upper estuary) was consistent between years and strongly predicted by photoperiod (as increasing day length), whereas water temperatures and flow rates were weak predictors and highly variable between years. Timings of river entry of individual shad were also consistent across consecutive spawning migrations, indicating high individual repeatability. The application of acoustic telemetry in this study thus revealed high repeatability in the timing of annual spawning migrations, which were cued mainly by increasing day length and that, being seasonally predictable, should ensure entry into freshwater with sufficient time to arrive in spawning areas when in-river environmental conditions are favourable.

Opportunities for improving feed efficiency and spinal health in New Zealand farmed Chinook salmon (Oncorhynchus tshawytscha) using genomic information - Megan Scholtens; Ken Dodds; Seumas Walker; Shannon Clarke; Mike Tate; Trevor Slattery; Mark Preece; Lorena Arratia; Jane Symonds (Aquaculture, 2023)

Intercontinental analysis of temperate steppe stream food webs reveals consistent autochthonous support of fishes - Emily R. Arsenault; James H. Thorp; Michael J. Polito; Mario Minder; Walter K. Dodds; Flavia Tromboni; Alain Maasri; Mark Pyron; Bud Mendsaikhan; Amarbat Otgonganbat; Solongo Altangerel; Sudeep Chandra; et al. (Ecology Letters, 2022)
Quantifying the trophic basis of production for freshwater metazoa at broad spatial scales is key to understanding ecosystem function and has been a research priority for decades. However, previous lotic food web studies have been limited by geographic coverage or methodological constraints. We used compound‐specific stable carbon isotope analysis of amino acids (AAs) to estimate basal resource contributions to fish consumers in streams spanning grassland, montane and semi‐arid ecoregions of the temperate steppe biome on two continents. Across a range of stream sizes and light regimes, we found consistent trophic importance of aquatic resources. Essential AAs of heterotrophic microbial origin generally provided secondary support for fishes, while terrestrial carbon did not seem to provide significant, direct support. These findings provide strong evidence for the dominant contribution of carbon to higher‐order consumers by aquatic autochthonous resources (primarily) and heterotrophic microbial communities (secondarily) in temperate steppe streams.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Behavioural Responses of a Large, Benthic Elasmobranch to Catch-and-Release Angling - Edward Lavender; Dmitry Aleynik; Jane Dodd; Janine Illian; Mark James; Peter J. Wright; Sophie Smout; James Thorburn (Frontiers in Marine Science, 2022)
Catch-and-release angling is widespread, but the impacts of this practice for captured individuals are understudied, especially among elasmobranchs. Studies on sub-lethal behavioural impacts are particularly sparse, despite their importance for the interpretation of biologging data and for assessments of species’ tolerance to capture. In this study, the behavioural responses of flapper skate ( Dipturus intermedius ) to catch-and-release angling were described for the first time, using archival observations (depth and temperature) for 21 tag deployment/retrieval events and five recreational angling events that occurred during tagged individuals’ time at liberty from charter vessels off the west coast of Scotland in 2016–17. During capture (8–50 minutes), the changes in depth and temperature experienced by individuals typically exceeded natural variability. Post-release, behavioural change was apparent from visual inspection, regression and functional data analysis of the time series. Immediately following release, movements into deeper water and short periods of low vertical activity (usually 1–2 hours in duration) were common. However, overall average vertical activity was typically around 38% higher in the 12 hours following release than in undisturbed activity. A small number of individuals (n = 3, 14%) exhibited irregular post-release behaviour in the form of rapid, transient re-ascents towards the surface following release. Collectively, the evidence for limited, short-term behavioural changes suggests that flapper skate behaviour is relatively resilient to catch-and-release angling from charter vessels, but irregular post-release behaviour in 14% of individuals is sufficiently notable to indicate that further research is required on the impacts of this practice. This study clearly demonstrates the value of biologging data and behavioural analyses for examining the impacts of disturbance and separating ‘disturbed’ and ‘undisturbed’ behaviours in studies of animal movement.

One beach amongst many: how weak fidelity to a focal nesting site can bias demographic rates in marine turtles - Joseph B. Pfaller; Sara M. Weaver; Kristina L. Williams; Mark G. Dodd; Matthew H. Godfrey; DuBose B. Griffin; S. Michelle Pate; C. George Glen; Campbell J. Nairn; Brian M. Shamblin (Marine Biology, 2022)

Environmental cycles and individual variation in the vertical movements of a benthic elasmobranch - Edward Lavender; Dmitry Aleynik; Jane Dodd; Janine Illian; Mark James; Peter J. Wright; Sophie Smout; James Thorburn (Marine Biology, 2021)
Trends in depth and vertical activity reflect the behaviour, habitat use and habitat preferences of marine organisms. However, among elasmobranchs, research has focused heavily on pelagic sharks, while the vertical movements of benthic elasmobranchs, such as skate (Rajidae), remain understudied. In this study, the vertical movements of the Critically Endangered flapper skate ( Dipturus intermedius ) were investigated using archival depth data collected at 2 min intervals from 21 individuals off the west coast of Scotland (56.5°N, −5.5°W) in 2016–17. Depth records comprised nearly four million observations and included eight time series longer than 1 year, forming one of the most comprehensive datasets collected on the movement of any skate to date. Additive modelling and functional data analysis were used to investigate vertical movements in relation to environmental cycles and individual characteristics. Vertical movements were dominated by individual variation but included prolonged periods of limited activity and more extensive movements that were associated with tidal, diel, lunar and seasonal cycles. Diel patterns were strongest, with irregular but frequent movements into shallower water at night, especially in autumn and winter. This research strengthens the evidence for vertical movements in relation to environmental cycles in benthic species and demonstrates a widely applicable flexible regression framework for movement research that recognises the importance of both individual-specific and group-level variation.

Corrigendum: Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)

Seasonal and Ontogenetic Variation in Depth Use by a Critically Endangered Benthic Elasmobranch and Its Implications for Spatial Management - James Thorburn; Peter J. Wright; Edward Lavender; Jane Dodd; Francis Neat; Julien G. A. Martin; Caroline Lynam; Mark James (Frontiers in Marine Science, 2021)
Seasonal and ontogenetic variations in depth use by benthic species are often concomitant with changes in their spatial distribution. This has implications for the efficacy of spatial conservation measures such as marine protected areas (MPAs). The critically endangered flapper skate ( Dipturus intermedius ) is the designation feature of an MPA in Scotland. This species is generally associated with deeper waters >100 m; however, little is known about its seasonal or ontogenetic variation in habitat use. This study used archival depth data from 25 immature and mature flapper skate tagged in the MPA over multiple years. Time series ranged from 3 to 772 (mean = 246) days. Generalised additive mixed models and highest density intervals were used to identify home (95%) and core (50%) highest density depth regions (HDDRs) to quantify depth use in relation to time of year and body size. Skate used a total depth range of 1–312 m, but home HDDRs typically occurred between 20 and 225 m. Core HDDRs displayed significant seasonal and ontogenetic variations. Summer core HDDRs (100–150 m) suggest high occupancy of the deep trenches in the region by skate of most size classes. There was an inverse relationship between body size and depth use and a seasonal trend of skate moving into shallow water over winter months. These results suggest that flapper skate are not solely associated with deep water, as skate, especially large females, are frequently found in shallow waters (25–75 m). The current management, which protects the entire depth range, is appropriate for the protection of flapper skate through much of its life history. This research demonstrates why collecting data across seasonal scales and multiple ontogenetic stages is needed to assess the effectiveness of spatial management.

In search of the “missing majority” of nesting loggerhead turtles: improved inter-seasonal recapture rates through subpopulation-scale genetic tagging - Brian M. Shamblin; Mark G. Dodd; S. Michelle Pate; Matthew H. Godfrey; Joseph B. Pfaller; Kristina L. Williams; Breanna L. Ondich; David A. Steen; Elizabeth S. Darrow; Paul Hillbrand; Ruth Boettcher; Michael S. Coyne; et al. (Marine Biology, 2021)

Preparing interdisciplinary leadership for a sustainable future - Christopher G. Boone; Steward T. A. Pickett; Gabriele Bammer; Kamal Bawa; Jennifer A. Dunne; Iain J. Gordon; David Hart; Jessica Hellmann; Alison Miller; Mark New; Jean P. Ometto; Ken Taylor; et al. (Sustainability Science, 2020)

Correction to: Are there any differential responses to concussive injury in civilian versus athletic populations: a neuroimaging study - Brian Johnson; Andrew Dodd; Andrew R. Mayer; Mark Hallett; Semyon Slobounov (Brain Imaging and Behavior, 2020)

Are there any differential responses to concussive injury in civilian versus athletic populations: a neuroimaging study - Brian Johnson; Andrew Dodd; Andrew R. Mayer; Mark Hallett; Semyon Slobounov (Brain Imaging and Behavior, 2020)

What can seabirds tell us about the tide? - Matthew Cooper; Charles Bishop; Matthew Lewis; David Bowers; Mark Bolton; Ellie Owen; Stephen Dodd (Ocean Science, 2018)
Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are consistent with their drifting with the tidal flows and changing direction as the flood turns to ebb and vice versa. Data from 4 years (2011–2014) have been binned in a geographical grid and analysed to give the variation of current over a mean tidal cycle in each grid element. A map of maximum current speed is consistent with a numerical model of the tidal currents in the region. The root mean square difference between observed maximum speed and that predicted by the model is 0.15 m s−1, about 15 % of typical current speeds in the area. The divergence between bird-track speed and model prediction increases in regions of the fastest tidal currents. The method clearly has its limitations, but the results of this study show that tagged birds resting on the sea have potential to provide relatively inexpensive quantitative information about surface tidal currents over an extended geographical area.

Climate Change and Consequences for Potato Production: a Review of Tolerance to Emerging Abiotic Stress - Timothy S. George; Mark A. Taylor; Ian C. Dodd; Philip J. White (Potato Research, 2017)

Elemental concentrations and in vitro bioaccessibility in Canadian background soils - Matt Dodd; G. Mark Richardson; Ross Wilson; Andy Rencz; Peter Friske (Environmental Geochemistry and Health, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Improved female abundance and reproductive parameter estimates through subpopulation-scale genetic capture-recapture of loggerhead turtles - Brian M. Shamblin; Mark G. Dodd; DuBose B. Griffin; S. Michelle Pate; Matthew H. Godfrey; Michael S. Coyne; Kristina L. Williams; Joseph B. Pfaller; Breanna L. Ondich; Kimberly M. Andrews; Ruth Boettcher; Campbell J. Nairn (Marine Biology, 2017)

Prioritizing plant eradication targets by re-framing the project prioritization protocol (PPP) for use in biosecurity applications - Aaron J. Dodd; Nigel Ainsworth; Cindy E. Hauser; Mark A. Burgman; Michael A. McCarthy (Biological Invasions, 2017)

Emotion moderates the association between HTR2A (rs6313) genotype and antisaccade latency - Mark Mills; Olivia Wieda; Scott F. Stoltenberg; Michael D. Dodd (Experimental Brain Research, 2016)

Identifying hotspots of alien plant naturalisation in Australia: approaches and predictions - Aaron J. Dodd; Michael A. McCarthy; Nigel Ainsworth; Mark A. Burgman (Biological Invasions, 2016)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Effects of long-term exposure to enriched CO2 on the nutrient-supplying capacity of a grassland soil - Roberta Gentile; Mike Dodd; Mark Lieffering; Shona C. Brock; Phil W. Theobald; Paul C. D. Newton (Biology and Fertility of Soils, 2012)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Tetranucleotide markers from the loggerhead sea turtle (Caretta caretta) and their cross-amplification in other marine turtle species - Brian M. Shamblin; Brant C. Faircloth; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Peter H. Dutton; Amy Frey; Campbell J. Nairn (Conservation Genetics, 2009)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.